2017
DOI: 10.1515/popets-2017-0047
|View full text |Cite
|
Sign up to set email alerts
|

UnLynx: A Decentralized System for Privacy-Conscious Data Sharing

Abstract: Current solutions for privacy-preserving data sharing among multiple parties either depend on a centralized authority that must be trusted and provides only weakest-link security (e.g., the entity that manages private/secret cryptographic keys), or leverage on decentralized but impractical approaches (e.g., secure multi-party computation). When the data to be shared are of a sensitive nature and the number of data providers is high, these solutions are not appropriate. Therefore, we present UnLynx, a new decen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 33 publications
0
65
0
Order By: Relevance
“…Systems relying on homomorphic encryption [11], [13], [16], [27], [28], [29] are often limited in the functionalities they offer (e.g., sum only). They present high-performance overhead in comparison with their less secure counterparts or still rely on honest-but-curious parties.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Systems relying on homomorphic encryption [11], [13], [16], [27], [28], [29] are often limited in the functionalities they offer (e.g., sum only). They present high-performance overhead in comparison with their less secure counterparts or still rely on honest-but-curious parties.…”
Section: Related Workmentioning
confidence: 99%
“…They present high-performance overhead in comparison with their less secure counterparts or still rely on honest-but-curious parties. In our previous work, we presented UnLynx [16], a decentralized system that enables the computation of (only) sums on distributed datasets and ensures DP s' privacy and data confidentiality. UnLynx assumes DP s to be honest-but-curious and, unlike Drynx, it does not ensure end results robustness.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…With ever‐increasing amounts of genetic data there are emerging regulatory issues regarding data safety and storage. Although cloud environments enable high‐capacity data storage (eg, Amazon Web Services, https://aws.amazon.com/), there are legitimate concerns about the privacy and security of sensitive cloud‐stored genetic data, indicating the need for more secure and decentralized solutions (eg, UnLynx) . Data sharing, which facilitates genotype‐phenotype correlation, is subject to further discussions as it has been shown that even after de‐identification, re‐identification of a single person is at least partially possible by either STR or SNP genotyping …”
Section: Regulatory Issues: Genetic Counseling Reimbursement and Datmentioning
confidence: 99%